Influência do exercício físico sobre variáveis funcionais, morfológicas e moleculares do coração de ratos idosos - Guirado, Gabriel Negretti [UNESP] (2014)
Structural and physiological changes occur in several organs and tissues during aging. In the heart, increase in interstitial collagen matrix and left ventricular diastolic dysfunction are the most frequent alterations. Whether these changes are part of aging process or induced or modulated by a sedentary life style is not established. Although physical training programs have been recommended to diseases prevention and cardiovascular rehabilitation, their effects on cardiac structures and function are not completely clear. Furthermore, there are few studies on the mechanisms involved in the beneficial effects of prolonged exercise on cardiac function. Purpose: To evaluate the effects of regular aerobic physical exercise on functional capacity, cardiac and myocardial function, and interstitial collagen matrix of aging rats. Methods: Male Wistar rats were assigned into three groups: 1) sedentary young (W6, n=24); 2) sedentary old (W21-Sed, n=25); and 3) exercised old (W21-Ex, n=20). Physical exercise was performed in treadmill for 12 weeks. In vivo cardiac evaluation was performed by echocardiography. Myocardial function was assessed in left ventricular (LV) papillary muscle preparation. In LV tissue, total and soluvel collagen concentration was evaluated by spectrophotometry. Protein expression of tipo I and III collagen and lysyl oxidase was analyzed by Western blot. Statistical analysis: ANOVA and Bonferroni or Kruskal-Wallis and Dunn, and Student t test. Results: At the end of the experiment, body weight was greater in W21-Sed and W21-Ex groups than W6. Anatomical variables did not differ between groups. Before training, functional capacity did not differ between aged groups. At the end of experment, W21-Ex group present higher distance and time in treadmill than W21-Sed e W6. W21-Sed group had worse physical capacity than W6. Thickness of LV diastolic posterior wall and interventricular septum and relative wall ...